Endocytosis in Saccharomyces cerevisiae: internalization of alpha-amylase and fluorescent dextran into cells. - Makarow, M (1985)
In the preceding paper I reported that Saccharomyces cerevisiae spheroplasts were able to internalize particulate markers, enveloped viruses, into intracellular organelles. Here the internalization of soluble macromolecules into cells having an intact cell wall is described. alpha-Amylase was taken up into cells in a temperature- and concentration-dependent way. The kinetics of accumulation were linear for the first 20-40 min at 37 degrees C and then started to level off. Internalization of alpha-amylase into spheroplasts displayed similar characteristics, but the accumulation rate was about four times higher than into cells. Fluorescent dextran was used to mark morphologically the compartment into which internalization occurred. This marker was accumulated into the vacuole of the cells in a time-, temperature- and concentration-dependent way. A temperature-sensitive mutant deficient in exocytosis was found to be defective in intracellular accumulation of alpha-amylase and dextran. At the restrictive temperature, very little alpha-amylase accumulated into the cells and only faint staining of intracellular organelles with fluorescent dextran could be detected. At the permissive temperatures, accumulation of alpha-amylase and dextran into the mutant cells was comparable with accumulation into wild-type cells. I conclude that alpha-amylase and fluorescent dextran were internalized into S. cerevisiae cells and directed into the vacuoles.